The effect of flash card media and problem-based learning to critical thinking skills in elementary school science lessons - Rudi Hermansyah Sitorus; Rita Kurnia; Dinda Widyastika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study examines the effect of flash card media and learning-based problem-solving on the critical thinking skills of students in Science Lessons, Grade V, Elementary School. This is an experimental study with a quantitative approach. The method used is quasi-experimental. Research design is a non-equivalent control group design. The research population involved all the students in Class V of State Elementary School 060970 Medan Belawan. The research sample consisted of 44 students from Classes VA and VB. The research results showed that the independent sample T-Test analysis of the post-test classes, both experimental and control, yielded a significant result. (2-tailed) is 0.000 while the level of significance α = 0.05. The results show a significant value since the value (2-tailed) < 0.05, it is concluded that Ha is accepted and H0 is rejected. This indicates an effect on improvement skills, critical thinking, student class experiments, and controls. It can be concluded that using flash card media and problem-based learning affects these skills, particularly in Class V students of SDN Negeri 060970 Medan Belawan.